The formation of a system of design and engineering organizations for the development of small arms and artillery in the USSR (1920s–1930s) - Timofeeva, Rimma Aleksandrovna (Исторический журнал: научные исследования, 2025)
The subject of this study is the initial stage of forming the national system of design and engineering organizations in the field of artillery. This period is fundamental in the process of establishing the principles of functioning of design bureaus within the system of scientific and technical organizations of the USSR. The stages of development of design bureaus (DB) of artillery specialization are considered, starting with the activities of the DB of the Special Artillery Testing Commission. The period of reorganization of artillery design bureaus, implemented at the turn of the 1920s and 1930s, when they were transferred from the jurisdiction of the People’s Commissariat for Military and Naval Affairs to the authority of the Supreme Council of National Economy, is characterized. A list of enterprises identified as the base for creating design bureaus is provided, and the contradictions of the first five years of their activities are determined. The complex of methods used included the processing of archival materials, historical-scientific analysis of foundational works, and comparative-historical methods. As a result of this research, using the example of artillery design bureaus, the main milestones in the formation of the system of design and research organizations that developed military equipment and armaments for the main branches of the Red Army or contributed to this activity were identified for the first time. Such organizations also existed under the Air Force, Navy, and others. An important conclusion is the indication that, in addition to design and engineering organizations, scientific research institutes operated within the same branches of the military, conducting research to find technical solutions that would enhance the effectiveness of the relevant types of armaments. The combination and coordination of the functioning of these organizations—design bureaus, research institutes, and test sites—established in the 1930s ensured the possibility of developing and setting up serial production of high-level weapon and military equipment samples of appropriate quality, many of which were groundbreaking on a global scale.